AN INVESTIGATION ON MOTORCYCLE WINDSHIELD DESIGNS FOR ENHANCED AERODYNAMIC FEATURE - Ma'arof M.I.N., M.I.N; Chaka, G.T; Yang, E.T.K. (IAEME Publication, 2018)
A motorcycle windshield protects motorcyclist from wind and external environment from making direct contact to the upper body extremities while riding. The windblast that has direct contact with the motorcyclist is considered to be a laminar flow. However, in the event of poor streamlining, the windshield would trap the turbulence instead and creates a higher dynamic pressure which affects its overall aerodynamic functionality. This study was aimed at investigating the different designs of windshield to minimize dynamic pressure to signify good aerodynamics characteristics. ANSYS-Fluent workbench was used to simulate the flow and optimize the streamline. It was observed that windshield with slot had lower performance compared to the design without slot due to the air passage through the slot that would subsequently alter the streamline and make the turbulence wake and output dynamic pressure to be higher. Consequently, the design with a smaller surface area would perform better due to less stagnation points